2006
DOI: 10.1073/pnas.0608586103
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric triple-shape materials

Abstract: Shape-memory polymers represent a promising class of materials that can move from one shape to another in response to a stimulus such as heat. Thus far, these systems are dual-shape materials. Here, we report a triple-shape polymer able to change from a first shape (A) to a second shape (B) and from there to a third shape (C). Shapes B and C are recalled by subsequent temperature increases. Whereas shapes A and B are fixed by physical cross-links, shape C is defined by covalent cross-links established during n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
392
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(395 citation statements)
references
References 18 publications
2
392
0
1
Order By: Relevance
“…The concept of polymeric composite, in which two or more layers of polymers with different transition temperatures, provides an alternative to achieve the multiple-SME [32]. By means of having two transition components with different transition temperatures, instead of having only one as in most of previous studies, in 2006, Professor Lendlein's group demonstrated a convenient approach to achieve the triple-SME [107]. In 2010, Dr. Xie demonstrated that a polymer with a broad transition temperature range can be programmed to have more than one intermediate shape [108].…”
Section: Multiple-sme (Shape Memory Effect)mentioning
confidence: 99%
“…The concept of polymeric composite, in which two or more layers of polymers with different transition temperatures, provides an alternative to achieve the multiple-SME [32]. By means of having two transition components with different transition temperatures, instead of having only one as in most of previous studies, in 2006, Professor Lendlein's group demonstrated a convenient approach to achieve the triple-SME [107]. In 2010, Dr. Xie demonstrated that a polymer with a broad transition temperature range can be programmed to have more than one intermediate shape [108].…”
Section: Multiple-sme (Shape Memory Effect)mentioning
confidence: 99%
“…For example, Lendlein reported that crosslinked poly(ε-caprolactone), which contained polyethylene glycol (PEG) as side chains (CLEG), could be inserted into the body as a removable stent used a compressed shape A, and when placed at a requisite position, the stent could be recovered to shape B, lastly it could contracted to shape C under the external stimulus for easy to remove. 24 Furthermore, future desired SMP devices will require multifunction, which includes multi-stimuli shape memory, triple shape memory, two-way SMP, and more. 25 SMPU based on poly(ε-caprolactone) (PCL) is a representative SMP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Conventional SMPs are designed to memorize only one permanent shape that corresponds to the most relaxed state of the switching segments, exhibiting the so-called dual-shape memory effect. The first example of triple-shape memory effect was reported by Bellin et al where two types of polymeric chains with discrete transition temperatures were incorporated within a crosslinked network (Bellin, 2006). One of the polymer networks containing poly(ε-caprolactone) (PCL) segments and poly(cyclohexyl methacrylate) (PCHMA) segments, named MACL, exhibited a T m around 50 ºC and a T g around 140 °C.…”
Section: Smps With Multi-shape Memory Effectmentioning
confidence: 99%